INFORMATION POTENTIAL OF THE LEADERSHIP DIAMOND MODEL: CONDITIONS OF ITS DETECTION AND USE IN PUBLIC ADMINISTRATION - Dmytro Dzvinchuk; Iryna Ozminska; Mariana Orliv; Petrenko, Victor (International Journal of Innovative Technologies in Social Science, 2021)
The article explores the information potential of the Leadership Diamond model and substantiates the conditions of its detection and use in public administration. The expediency of supplementing traditional assessment of leadership interpretation of the vision, ethics, reality, and courage scores under the Leadership Diamond model with additional (secondary) scores through deepening their common interpretation is justified. A new interpretation allows assessing the overall level of leadership of an individual (the level of approximation to the norm of Great Leader) and four derivative additional characteristics (levels of fairness and reliability, moderation and selflessness, courage and piety, wisdom and ability). The proposed method of interpretation provides with an opportunity and information for analytical research and comparison of individual and group scores, identification of personal and group minimum (weaknesses) and maximum (strengths), allows making decisions on substantiated selection, the formation of individual and group development trajectories, improvement and correction of leadership skills of public servants. Therefore, the perspective of further research is the use of this method to develop the level of wisdom and ability of public servants through design thinking methodology.